Modelling sources of operational noise in production systems - Afy-Shararah, Mohamed; Patsavellas, John; Salonitis, Konstantinos (Elsevier, 2021)
This paper aims to identify and model the sources of operational noise that contribute to unstable and poor flow of materials in production systems. 80 interviews with managers and decision-makers were conducted and analyzed and have revealed that internal technical instabilities, employee variability, and customer and supplier uncertainty are the major sources of operational noise. They have also identified the relationships between the different variables of a production system that contribute to the amplification of operational noise and hence should be managed effectively to ensure a smooth flow in manufacturing operations.
Keywords: Causal Loop Diagrams; Operational Noise; Production Systems; Flow